2016
DOI: 10.1088/1361-6579/38/1/15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac magnetic resonance imaging and bio-impedance spectroscopy for the assessment of fluid displacement induced by external leg compression

Abstract: Heart failure is marked by frequent hospital admissions, often as a consequence of pulmonary congestion. Current gold standard techniques for thoracic fluid measurement require invasive heamodynamic access and therefore they are not suitable for continuous monitoring. Changes in thoracic impedance (TI) may enable non-invasive early detection of congestion and prevention of unplanned hospitalizations. However, the usefulness of TI to assess thoracic fluid status is limited by inter-subject variability and by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Our results, together with previous studies, suggest that may be an adequate parameter for monitoring early to late stages thoracic fluid accumulation due to its sensitivity to vascular, interstitial, alveolar and pleural fluids. Our early findings on the correlation between and pulmonary blood volume assessed by MRI are available in [40]. Use of additional parameters e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, together with previous studies, suggest that may be an adequate parameter for monitoring early to late stages thoracic fluid accumulation due to its sensitivity to vascular, interstitial, alveolar and pleural fluids. Our early findings on the correlation between and pulmonary blood volume assessed by MRI are available in [40]. Use of additional parameters e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that variations in pulmonary blood volume and PTT can be accurately evaluated using MRI . Moreover, normalized left atrial transit times are correlated with invasive left ventricular pressure measurements .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Previous research has shown that variations in pulmonary blood volume and PTT can be accurately evaluated using MRI. [10][11][12][13] Moreover, normalized left atrial transit times are correlated with invasive left ventricular pressure measurements. 14,15 CEUS-derived PTT correlates well with true volumes in an in-vitro setup, 16 with PTT measured via MRI and with levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP).…”
Section: Introductionmentioning
confidence: 99%